Insights into the Accounting Conservatism Literature: A Selective Criteria Analyzing (Global Journal of Management and Business Research, 2016)
This study attempts to present a literature review for accounting conservatism that is considered one as of the most ancient and debatable terms in accounting research. Based on several academic studies the theoretical background propose an examination for accounting conservatism which consists of definition, explanations for existence raisons of accounting conservatism and gives measurement models in order to provide a better insight. It is also contribute on the growing literature investigating the role of conditional conservatism in the value of equity markets. Starting from the idea that the conditional accounting conservatism is characterized by an asymmetric recognition of positive and negative economic news we present respectively some sources of conditional accounting conservatism; the goodwill impairment, long-lived asset impairment, inventory recorded at the lower of cost or market and asymmetry in gain/loss contingencies.
Keywords: accounting conservatism; conditional conservatism; conservatism measurement